Distraction With Virtual Reality Goggles in Paediatric Dental Treatment: A Randomised Controlled Trial - Lior Zaidman; Gal Lusky; Aviv Shmueli; Elinor Halperson; Moti Moskovitz; Diana Ram; Avia Fux-Noy (Elsevier, 2023)
Aim: The aim of this study was to examine whether screening content through virtual reality (VR) goggles can diminish pain perception during local anaesthesia administered using the inferior alveolar nerve block technique and rubber dam placement in routine paediatric dental treatment. Materials and methods: This is a crossover study of healthy 4- to 12-year-old children who were scheduled to receive local anaesthesia administered using the inferior alveolar nerve block technique and rubber dam placement in 2 visits. The participants were randomly assigned to undergo 1 treatment performed with Oculus GO VR goggles and the other treatment without. Pain was evaluated using the Wong-Baker FACES Pain Rating Scale and the Modified Behavioral Pain Scale (MBPS). Results: The study group included 29 children with a mean age of 8.29 years (SD, 1.96). Whilst administering local anaesthesia, no significant difference was observed in the Wong-Baker FACES Pain Rating Scale and in MBPS movements between visits with and without the VR goggles. However, significantly lower pain perception was observed in the other parameters of MBPS when using the VR goggles: Face (P = .007) and Cry (P = .046). During placement of a rubber dam, significantly less pain was reported by the patients (P = .005) and observed by the assessor (Face [P = .005], Cry [P = .029], and Movement [P = 0.028]) when the VR goggles were used. Conclusions: VR can decrease pain perception during rubber dam placement in children, but it has limited benefit during administration of local anaesthesia.